InfoSec career hacking : sell your skillz, not your soul - Bayles, Aaron W. (Syngress Pub., 2005)
Do you spend hours coding on an application for the sheer joy and challenge? How about taking the time to analyze every piece of traffic that crosses your network, dissecting packets, and making sure nothing hidden is going on? If you want to refine these skills (and learn many new ones) to build an InfoSec career in a top corporation or government agency but aren't sure where to begin, this book is for you! The authors of this book have all succeeded in applying their inherent, hacker skills to build successful InfoSec careers. From them, you will learn about the many, different jobs availabl.